2019
DOI: 10.4238/gmr18214
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Combining ability in snap bean lines in Brazil

Abstract: The search for genetic material of snap beans with desirable yield traits is of utmost importance for yield increase in Brazil. We evaluated 12 snap bean genotypes by diallel crosses that presented characteristics of interest, so as to select the best genitors to generate productive populations in the snap bean breeding program of the Universidade Estadual do Norte Fluminense in Rio de Janeiro state, Brazil. Diallel crosses were performed applying Method 2 of Griffing. The F 1 generation, composed of 36 hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
1
0
1
Order By: Relevance
“…GCA and SCA effects are determined according to the differences between parents and crosses from the general average. The results we obtained are largely similar to the results obtained in the of Ceyhan and coauthors (2014a,b), Kepildek and Ceyhan (2021), Oliveira Junior and coauthors (1997), Ceyhan and Şimşek (2021), Arunga and coauthors (2014), Senbetay and Tesfaye (2015), Gomes and coauthors (2019), and Tamüksek and Ceyhan (2022) [12][13][14]23,25,28,30,32,33].…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…GCA and SCA effects are determined according to the differences between parents and crosses from the general average. The results we obtained are largely similar to the results obtained in the of Ceyhan and coauthors (2014a,b), Kepildek and Ceyhan (2021), Oliveira Junior and coauthors (1997), Ceyhan and Şimşek (2021), Arunga and coauthors (2014), Senbetay and Tesfaye (2015), Gomes and coauthors (2019), and Tamüksek and Ceyhan (2022) [12][13][14]23,25,28,30,32,33].…”
Section: Resultssupporting
confidence: 86%
“…The fact that ʋ 2 GCA/ʋ 2 SCA greater than 1 and H/D 1/2 1 for the number of seeds per plant and hundred-seed weight in the plant shows the additive gene effect (Table 2). Additive gene effects for these traits in bean have been reported in previous studies by Arunga and coauthors (2014), Senbetay and Tesfaye (2015) and Gomes and coauthors (2019) [30,32,33]. In contrast to our finding, Ceyhan and coauthors (2014a,b), Kepildek and Ceyhan (2021), Oliveira Junior and coauthors (1997), and Ceyhan and Şimşek (2021) reported that the nonadditive gene effect and the dominant gene effect were effective in the inheritance of number of seeds per plant and hundred-seed weight of the bean plant [12][13][14]25,28].…”
Section: Resultsmentioning
confidence: 58%
“…Estas altas y positivas estimaciones de ĝi y promedio per se muestran una alta varianza aditiva, lo que convierte a estos progenitores en fuertes candidatos para producir buenas progenies. Estos resultados son similares a los encontrados por Gomes et al (2019), quienes afirmaron que los efectos ĝi positivos son indicadores útiles para el carácter LDV y, posteriormente, sugirieron que estos podrían ser explotados para la obtención de líneas superiores de habichuela.…”
Section: Efectos De La Habilidad Combinatoria General (ĝI)unclassified